Efektivitas Pengunaan Media Pop Up Book Audiovisual Tata Cara Sholat untuk Anak TK - Nadia Michelle; Nan Rahminawati; Dewi Mulyani (Jurnal Riset Pendidikan Guru Paud, 2023)
Abstract. This research is intended to see the extent of the understanding and abilities of group B chilDren aged 5-6 years in Al-Fithroh Kindergarten in carrying out prayer activities in early childhood which are usually applied in Al-Fithroh Cipaganti Kindergarten. The method used in this study is a quasi-experimental research method with a quantitative research approach, comparing the learning that is usually applied by teachers, namely without media and learning with researchers who use learning media related to student achievement in understanding prayer activities and the ability to carry out prayer activities. Data collection techniques through interviews, observations/observations, document searches and questionnaires. Data analysis techniques used in experimental analysis through data analysis Data collection, population normality test, normality test, data presentation and conclusion. The results of this study indicate that student achievement in understanding prayer activities and the ability to carry out prayer activities using learning media in the form of an Audiovisual Pop Up Book about prayer procedures shows a good increase, inversely proportional to the results of student achievement applied learning without media has not shown a significant increase. big. The participation of chilDren and parents as well as teachers in prayer learning development activities was very responsive and showed a positive response. So that the results achieved are in accordance with what is expected. Abstrak. Penelitian ini dimaksudkan untuk melihat sejauh mana pemahaman dan kemampuan anak kelompok B usia 5-6 tahun di TK Al-Fithroh dalam melakukan kegiatan ibadah sholat pada anak usia dini yang biasa diterapkan di TK Al-Fithroh Cipaganti. Metode yang digunakan dalam penelitian ini adalah metode penelitian quasi eksperimen dengan pendekatan penelitian kuantitatif, membandingkan antara pembelajaran yang biasa diterapkan oleh guru yaitu tanpa media dengan pembelajaran dengan peneliti yang menggunakan media pembelajaran terkait tentang pancapaian siswa dalam memahami kegiatan ibadah sholat dan kemampuan melaksanakan kegiatan sholat. Teknik pengumpulan data melalui wawancara, pengamatan/observasi, penelusuran dokumen dan kuesioner. Teknik analisis data yang digunakan secara analisis eksperimen melalui Analisis Data Pengumpulan data, Uji Normalitas Populasi , Uji normalitas, Penyajian data dan Penarikan kesimpulan Hasil penelitian ini menunjukkan bahwa pancapaian siswa dalam memahami kegiatan ibadah sholat dan kemampuan melaksanakan kegiatan sholat menggunakan media pembelajaran berupa Pop Up Book Audiovisual tentang tata cara ibadah sholat menunjukkan peningkatan yang bagus, berbanding terbalik dengan hasil pencapaian siswa yang diterapkan pembelajaran tanpa media belum menunjukkan peningkatan yang besar. Partisispasi anak dan orangtua serta guru-guru dalam kegiatan pengembangan pembelajaran ibadah sholat ini sangat responsif dan menunjukkan respon yang positif. Sehingga hasil yang dicapai sesuai dengan apa yang diharapkan.